Environmentally Robust Memristor Enabled by Lead‐Free Double Perovskite for High‐Performance Information Storage. Issue 49 (31st October 2019) - Cheng, Xue‐Feng; Qian, Wen‐Hu; Wang, Jia; Yu, Chuang; He, Jing‐Hui; Li, Hua; Xu, Qing‐Feng; Chen, Dong‐Yun; Li, Na‐Jun; Lu, Jian‐Mei
Abstract: Memristors are emerging as a rising star of new computing and information storage techniques. However, the practical applications are severely challenged by their instability toward harsh conditions, including high moisture, high temperatures, fire, ionizing irradiation, and mechanical bending. In this work, for the first time, lead‐free double perovskite Cs2 AgBiBr6 is utilized for environmentally robust memristors, enabling highly efficient information storage. The memory performance of the typical indium‐tin‐oxide/Cs2 AgBiBr6 /Au sandwich‐like memristors is retained after 1000 switching cycles, 10 5 s of reading, and 10 4 times of mechanical bending, comparable to other halide perovskite memristors. Most importantly, the memristive behavior remains robust in harsh environments, including humidity up to 80%, temperatures as high as 453 K, an alcohol burner flame for 10 s, and 60 Co γ‐ray irradiation for a dosage of 5 × 10 5 rad (SI), which is not achieved by any other memristors and commercial flash memory techniques. The realization of an environmentally robust memristor from Cs2 AgBiBr6 with a high memory performance will inspire further development of robust electronics using lead‐free double perovskites. Abstract : Double perovskite Cs2 AgBiBr6 is fabricated into an indium tin oxide/Cs2 AgBiBr6 /Au device for the first time. Ultrastable memristive behavior is obtained owing to the tough crystallinity of Cs2 AgBiBr6 . Humidity‐, high temperature‐, fire‐, and radiation‐resistant properties of Cs2 AgBiBr6 ‐based devices promote memristive devices to work in harsh environments, where most perovskite‐based devices may fail to work.